PTU-011 A prospective audit of a speciality registrar led out of hours endoscopy service for suspected acute upper gastrointestinal bleeding. (17th June 2017) - Beinortas, T; Subramanian, V; Irvine, A; Venkatachalapathy, SV; Kane, JS; Mohammed, N; Rembacken, B; Everett, S; Burr, N; Sood, R
Abstract : Introduction: Acute upper gastrointestinal bleeding (AUGIB) is a potentially life threatening condition, resulting in 7.4% all-cause mortality in patients receiving endoscopy in the UK National audit in 2007 [1]. Formal, out-of-hours (OOH) endoscopy rotas for AUGIB are typically delivered by consultant gastroenterologists and have been shown to reduce waiting time to endoscopy and improve mortality. Leeds Teaching Hospitals NHS Trust (LTHT) has a Speciality registrar (SpR) led OOH on-call rota staffed by junior SpRs supervised by more senior trainees. We prospectively audited the LTHT SpR led OOH AUGIB service against the latest BSG National Audit results. Method: We included adult patients (>16 years), presenting to LTHT between March and September 2016 with a suspected AUGIB having an endoscopy procedure performed by a SpR alone, SpR supervising SpR or SpR supervised by consultant. Baseline clinical, laboratory, demographic data, grade of endoscopist, place of endoscopy, findings of endoscopy and treatments applied were recorded. The primary outcome was 30 day all-cause mortality. Secondary outcomes were 60 and 90 day all-cause mortality, re-bleed rates and time to endoscopy. We used hazard ratios and multiple logistic regression analysis to examine the association between any of our collected variables, 30 day all-cause mortality and re-bleed rates. We classified a p-value of <0.05 as being statistically significant. Results: 177 patients (62% male, median age 67, range 18–97) were included in the study. 54% of endoscopies were performed by two SpRs, 41% by SpR alone and 5% by SpR supervised by a consultant. Median time to endoscopy was 16.3 hours and 22% were performed in theatre. 30, 60 and 90 day mortality were, 5.1%, 5.1% and 9.0% respectively with 8.9% patients having a re-bleed. Low baseline albumin predicted 30 day mortality: HR 1.25 (95% CI, 1.05–1.50) per 1 g/L drop. AIMS65, Blatchford, pre-endoscopy Rockall scores and other baseline laboratory tests were not statistically significantly associated with 30 day mortality or re-bleed rates, although there were few events. Conclusion: An SpR-led OOH endoscopy rota compared favourably to national audit results for time to endoscopy, re-bleed and mortality. None of the prognostic scores demonstrated a statistically significant correlation with mortality rate. Where service configuration permits, the implementation of an SpR led AUGIB service may provide a model for exposure to training in AUGIB for Gastroenterology SpRs. Reference: . Hearnshaw SA, Logan RFA, Lowe D, et al. Acute upper gastrointestinal bleeding in the UK: patient characteristics, diagnoses and outcomes in the 2007 UK audit. Gut2011;60(10):1327–35 Disclosure of Interest: None Declared